Research on frost resistance of seawater sea-stone concrete. Issue 5 (May 2019) - Cai, Hong-ming; Qing, WU; Shen, Lin
Abstract: In this paper, the frost resistance of C30 seawater sea-stone concrete (SSC) under double corrosion in Marine environment is studied. In this paper, the relative dynamic modulus of elasticity, mass loss, micro morphology and composition of artificial sea water were tested and analyzed. The results show that under the condition of water conservation, SSC mass loss of 5% or more when chloride ions reduce after 40 times of freeze-thaw cycle.The freeze-thaw cycles of the quality loss and relative dynamic modulus of elasticity loss model are established respectively. The microscopic analysis of concrete in sea water stone are done, added to concrete in freeze-thaw and external double seawater corrosion performance.